Case report: A rare case of IgA nephropathy associated with type II Abernethy malformation - Cao, Wenya; Guo, Xiaoli; Zhao, Xue; Gao, Yi (Frontiers in Medicine, 2025)
Abernethy malformation is a rare congenital vascular anomaly involving extrahepatic portosystemic shunting, with only a handful of reported cases coexisting with IgA nephropathy. We present a case of a patient who initially manifested with proteinuria and hematuria, and later developed hepatic encephalopathy, prompting vascular imaging that identified a type II Abernethy malformation characterized by an extrahepatic portocaval shunt. A diagnosis of type II Abernethy malformation was established. The patient underwent laparoscopic partial shunt disconnection, which led to a marked reduction in proteinuria (from 0.8–2.1 g/d to 0.19–0.29 g/d). This case, along with previous reports, suggests that portosystemic shunting in Abernethy malformation may be a pathogenic factor in IgA nephropathy. Surgical correction of the shunt may confer renal benefits in selected cases and deserves further investigation.